ISPO: A Serious Game to train the Interview Skills of Police Officers - Manuel Guimarães; Rui Prada; Pedro A. Santos; João Dias; Cristina Soeiro; Raquel Guerra; Christina Steiner-Stanitznig; Andrea Molinari (Serious Games Society, 2022)
The Interview Simulation for Police Officers (ISPO) is a serious game developed to train police officers in communication competencies related to the interview of victims, witnesses and suspects. It was developed by Gameware Europe in collaboration with the Portuguese Police (Policia Judiciaria) within the RAGE project. The ISPO serious game was created using the modern methodologies and practices that are used in real-life police interviews. The focus of the game is on the training of communication competencies regarding gathering information from both victims and offenders. In order to evaluate the training effectiveness of the game, we conducted a study with 194 participants where general subjective learning effectiveness, using the Perceived Competence subscale of the IMI questionnaire, and domain-specific subjective learning effectiveness using the Police Interview Competency Inventory (PICI) were measured. Overall, ISPO improved the self-perceived competence of its players. Additionally, participants changed their opinion about the attitude to conduct a successful interview. Participants' level of importance attributed to being dominant diminished and the level of importance attributed to being more benevolent and communicative during police interviews increased. Effects were stronger in inexperienced users leading us to believe that the game is an added value for use in a police officer school.